2022
DOI: 10.1039/d1gc04581d
|View full text |Cite
|
Sign up to set email alerts
|

Bis(2-methoxyethyl)ether promoted intramolecular acceptorless dehydrogenative coupling to construct structurally diverse quinazolinones by molecular oxygen

Abstract: A simple, efficient, and clean approach for the synthesis of diverse dihydroisoquinolino[2,1-a]quinazolinones, 2-aryl quinazolinones, and analogues through intramolecular acceptorless dehydrogenative coupling has been achieved. The combination of bis(2-methoxyethyl)ether and molecular...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Up to date, diverse methods have been developed to synthesize these compounds with different substituents for a significant role in drug synthesis. Classical substrates for the synthesis of quinazolinones include, but are not limited to, 2-nitrobenzamides, 2-aminobenzamides, , 2-halobenzamides, 2-aminobenzophenones, 2-aminobenzonitriles, , and 2-halobenzoic acids. However, due to the selectivity of dehydrogenation processes during the synthesis, these types of reactions are generally carried out at high temperatures (usually above 100 °C) or using noble-metal catalysts (such as Ir, Pd, or Ru). Therefore, the design and development of new catalysts with high efficiency and easy availability are of great significance in the field of quinazolinone-based compound synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Up to date, diverse methods have been developed to synthesize these compounds with different substituents for a significant role in drug synthesis. Classical substrates for the synthesis of quinazolinones include, but are not limited to, 2-nitrobenzamides, 2-aminobenzamides, , 2-halobenzamides, 2-aminobenzophenones, 2-aminobenzonitriles, , and 2-halobenzoic acids. However, due to the selectivity of dehydrogenation processes during the synthesis, these types of reactions are generally carried out at high temperatures (usually above 100 °C) or using noble-metal catalysts (such as Ir, Pd, or Ru). Therefore, the design and development of new catalysts with high efficiency and easy availability are of great significance in the field of quinazolinone-based compound synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] There are various strategies reported in the literature for the construction of this valuable scaffold. [10][11][12][13][14][15][16] In particular, MCR between isatoic anhydrides, anilines, or ammonium acetate and carbonyl compounds is an important strategy in quinazolinone synthesis. With the help of this important MCR, different synthetic approaches have been developed using both homogeneous and heterogeneous catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…A survey of the literature indicated that 1,2-fused/disubstituted benzimidazoles can be prepared by several different strategies (Scheme ): (a) intramolecular sp 2 C–H amidation/amination of imines derived from o -phenylenediamine derivatives and aldehydes and promoted by iodine reagents or under copper-catalyzed aerobic conditions; (b) annulation of o -phenylenediamines with aldehydes or alcohols in the presence of Lewis acids, ionic liquids or transition-metal catalysts; (c) coupling or oxidative cyclization of N -alkyl- N ′-arylamidine substrates; (d) intramolecular C–H amination of readily accessible 2-amino or 2-nitro substituted aniline precursors achieved by oxidants such as m -CPBA, H 2 O 2 , and TEMPO, or under electrochemical, reductive redox cyclization, or transitionmetal-catalyzed conditions; (e) annulation of 2-aminopyridines with cyclohexanones, 2-iodoarylboronic acids or arenes; and (f) modification of the preformed benzimidazole frameworks . In view of the importance of 1,2-fused/disubstituted benzimidazoles, new and practical synthetic approaches to access compounds of this type are still highly desirable and should benefit the drug discovery field.…”
mentioning
confidence: 99%